Influences of governance and economic development level on happiness in high income Asian and European countries - Muhammad Asraf, Abdullah; Kueh, Jerome Swee Hui; Audrey, Liwan; Rosita, Binti Hamdan; Chan, Cathrine Bao Hui (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This study explores the relationship between governance and human development indicators with happiness using the panel data fixed effect and random effect estimation approach. Findings from the study stress on the importance of good governance in influencing life satisfaction. In a way, good governance stimulates happiness in a positive manner. Governments in developed countries in Asia and Europe may increase happiness and promote equality through enhancement in the quality of governance. This can be done by ensuring good practices in managing the economy and resources of the country. However, the relationship between the economic development level and happiness is inconclusive and insignificant.